2008
DOI: 10.1038/mi.2008.44
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the predominant antigenic epitopes in intestinal flora in IBD

Abstract: The normal intestinal flora is required for the development of intestinal inflammation in animal models of inflammatory bowel disease (IBD). In humans, several studies indicated a potential association of Escherichia coli (E. coli) with IBD. In addition, we have shown that T-cell clones of IBD patients cross react toward different enteric bacterial species and thus likely respond to conserved bacterial antigens. Therefore, we hypothesized that highly conserved E. coli proteins might be a reasonable candidate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…[ 2 ] showed that individual T cell clones from IBD patients were reactive to Bacteroides thetaiotaomicron , Bifidobacterium bifidum , Escherichia coli , and Yersinia enterocolitica . In 2008, Duchmann and colleagues [ 3 ] expanded their studies on antigenic epitopes by screening T helper cells from healthy subjects and from patients with Crohn’s disease and ankylosing spondylitis. However, none of these studies identified the actual epitope that stimulate the T cell.…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 ] showed that individual T cell clones from IBD patients were reactive to Bacteroides thetaiotaomicron , Bifidobacterium bifidum , Escherichia coli , and Yersinia enterocolitica . In 2008, Duchmann and colleagues [ 3 ] expanded their studies on antigenic epitopes by screening T helper cells from healthy subjects and from patients with Crohn’s disease and ankylosing spondylitis. However, none of these studies identified the actual epitope that stimulate the T cell.…”
Section: Introductionmentioning
confidence: 99%
“…studies conducted in various mouse models of IBDs have shown that most immunoregulatory events in mucosal inflammation are controlled by T-cells, that mucosal T-cell activation is antigen-dependent and the responsible antigens originate from intestinal bacteria [6][7][8]. MadCAM-1 and ICAM-1) on vascular endothelium and integrins (e.g.…”
Section: Figure 1 Putative Mechanisms Involved In the Accumulation Ofmentioning
confidence: 99%
“…Dysregulated responses to ingested food is perhaps more clearly revealed in patients with celiac disease-where patients with the risk haplotype exhibit an uncontrolled sensitivity to gluten antigens resulting in intestinal inflammation, villous atrophy, and crypt hyperplasia [20]. In IBD, the antigen provoking the exacerbated and uncontrolled inflammatory response is not known, although there is some evidence suggesting that Crohn's disease patients may have lost tolerance to their own commensal bacterial flora [21,22]. Loss of tolerance to autologous flora could be a primary defect or arise simply as a secondary effect following some other dysregulated inflammatory stimulus or barrier function defect in the intestine.…”
Section: Introductionmentioning
confidence: 99%